2016
DOI: 10.21149/spm.v58i2.7796
|View full text |Cite
|
Sign up to set email alerts
|

Proposals for the prevention of lung cancer in the health system of Mexico

Abstract: The management of lung cancer is challenging. However, nowadays the main goal is to achieve a significant overall survival accompanied by a good quality of life. Because smoking is associated with up to 71% of cancer deaths, the first policy that should be established is one that promotes strategies for healthy lifestyles by providing information about lung cancer, risk factors, protection factors, and precautionary data. Furthermore, an effective screening method that would allow early diagnosis should be est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 29 publications
0
10
0
3
Order By: Relevance
“…Likewise, this factor, limit the information we can get to describe the availability of resources for early diagnosis and treatments access, in order to improve the survival of these patients. 19,20 On the other hand, a risk factor associated with the presence of LC is tobacco, as mentioned in multiple studies. This exposure has decreased over time, both globally and in our country.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, this factor, limit the information we can get to describe the availability of resources for early diagnosis and treatments access, in order to improve the survival of these patients. 19,20 On the other hand, a risk factor associated with the presence of LC is tobacco, as mentioned in multiple studies. This exposure has decreased over time, both globally and in our country.…”
Section: Discussionmentioning
confidence: 99%
“…Nadler et al [16] also observed that patients with actionable mutations derived greater survival benefit from targeted therapies: 24.3 months in patients who received first-line targeted therapy versus 11.7 months for chemotherapy. As stated by Arrieta et al [23], following diagnosis, Mexican patients should be genotyped to identify predisposing mutations and receive personalized treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Derivado del análisis de los factores de riesgo relacionados con el cáncer pulmonar, los estudios publicados han identificado como estrategias primordiales para su prevención el fortalecimiento de las políticas para el control del tabaco, la reducción de la exposición a conta- minación por la combustión incompleta de combustibles fósiles y la mejora de la detección temprana. 13,14 En relación con la implementación de estrategias de prevención, el gobierno mexicano ha firmado y ratificado la Convención Marco de la Organización Mundial de la Salud para el Control del Tabaco (CMCT de la OMS), promulgado leyes federales como la Ley General para el Control del Tabaco (LGCT), leyes estatales que promueven los ambientes 100% libres de humo de tabaco, el incremento de los impuestos a los productos de tabaco y la implementación de advertencias sanitarias con pictogramas en las cajetillas de tabaco. [15][16][17][18] Respecto al control de factores relacionados con la salud ocupacional, se han publicado normas para controlar los agentes químicos en el ambiente laboral y modificado aquéllas que tienen como objetivo medir los niveles de contaminación ambiental.…”
Section: Medidas De Prevenciónunclassified